Variations in patient satisfaction with care for breast, lung, head and neck and prostate cancers in different cancer care settings - Charalambous, Andreas (My University, 2013)
Purpose of the research: To assess cancer patients' satisfaction and the extent to which it varies between cancer care centres. Methods and sample: This is a multi-site descriptive study reporting on the satisfaction of patients with breast, prostate, head and neck and lung cancers in Cyprus. The sample consisted of 272 patients randomly selected. Data were retrieved with the Patient satisfaction Scale additionally to 7 single questions reflecting 7-care dimensions namely "access to care", "explanation at first visit", "understanding of diagnosis and treatment", "first treatment: respect communication and involvement", "first treatment: pain and discomfort", "first treatment: hospital management" and "discharged co-ordination". Results: Participants were overall satisfied by the nursing care (mean 3.5) however, dissatisfaction was expressed in relation to the 7-care dimensions (p<0.001). Variations in satisfaction were found across the oncology settings as well as across cancer types. The variables gender, age, marital status, level of education, length of stay in the department, previous hospitalization, tumour type and treatment type had an influence on patients' perceived satisfaction (p<0.001). Conclusions: Seemingly identical nursing care can be measurably different between cancer care centres. Based on the findings the satisfaction variations can be attributed to factors personally experienced by the patients as well as to systemic hospital-level factors. The notion of patient satisfaction is important to clinical practice as a tool to assess and plan the nursing care and managers should bear in mind that patient satisfaction is sensitive to person specific variables as well as to many extraneous variables.
Keywords: Cancer care; Nursing care; Oncology settings; Patient satisfaction; Survey